اختلافات الأصوليين في القواعد المتعلقة بالصبي المميز وتطبيقاتها الفقهية المعاصرة - نصر، دسوقي يوسف دسوقي (جامعة الإمام محمد بن سعود الإسلامية, 2017)
تعتبر مرحلة الطفولة مرحلة هامة في التشريع الإسلامي. وقد تناول الفقهاء والاصوليون الصبي بمزيد من العناية والاهتمام في كثير من الاحكام الفقهية احكام العبادات والمعاملات وأحكام الاسرة والجنايات والحدود. وقد رأي الباحث أن اكر اهتمام الباحثين قديماً وحديثاً من ناحية الصبي المميز تتركز علية من الناحية الفقهية فقط. فرأي أن يتحدث عن اختلافات الأصوليين في القواعد المتعلقة بالصبي المميز. وكيف كان لهذا الاختلاف بينهم أثر كبير في كثير من أبواب الفقه الإسلامي. وأثر ذلك في الفروع الفقهية المبنية على تلك الاختلافات الأصولية. ويقف هذا البحث على تعريف الصبي المميز والصبي الغير مميز والفرق بينهما وبين البالغ كما يبين أن مناط التكليف في التشريع الإسلامي هو البلوغ والعقل. وليس التمييز حي يختلف التمييز من ثبي إلى أخر بحسب النشأة والبيئة والثقافة؛ إذ لا يمكن الوقوف بغتةً على الحد الذي يفهم به خطاب الشارع، فربط الشارع ذلك بالبلوغ والعقل. ويحصر البحث القواعد التي تدور حول الصبي المميز في ثلاث قواعد كلية هي: (لا تكليف قبل البلوغ)، (وقول الصبي لا حكم له)، (وفعل الصبي معتبر)، ويذكر الباحث تطبيقات لها من خلال ذكر الفروع الفقهية المبنية على تلك القواعد. وكيف راعي الشرع الحكيم المصالح في تصرفات الصبي المميز النافعة فاعتبرها وحافظ عليها. وتجنب المفاسد المترتبة على أقواله وافعاله الضارة علية، فلم يعتد بها وصارت لاغية.
Childhood is an important stage in Islamic legislation. Scholars and jurists addressed youth issues with more care and interest in many of the laws of jurisprudence in terms of quranic laws of worship, of transactions (Al- Muamalat), of family, of offenses and fixed punishments. The researcher finds that most of researchers' interest, in the past and present, regarding the discriminating boy's focused on the Jurisprudential aspect only. Thus, the researcher investigates fundamentalist's differences in the rules relating to the discriminating boy, and how these differences seriously affected many central issues of Islamic jurisprudence as well as their impact on the secondary issues of jurisprudence based on those fundamentalist differences. This research defines the discriminating and then on-discriminating boy, the difference between them, and the pubescent. It also shows that the basis of legal responsibility (Al-Takleef)in Islamic legislation is legal age and sanity, not perception which differs from one child to another according to the upbringing, environment, and culture. So, it is impossible to decide arbitrarily on the point intended by the legislator. Therefore, this has been connected to legal age and sanity. The research conflicts the rules regarding the discriminating boy in to throe comprehensive ones; no legal responsibility (Takleef) before legal age; the juvenile’s saying doesn't count; and the juvenile’s deed is to be considered. The researcher gives some applications by mentioning the branches of jurisprudence based on those rules. He also explains how the legislation takes into account what is beneficial to public interest in the behavior of the discriminating boy, maintains it, and avoids the consequential damage to society of his wrong sayings and deeds, which are insignificant and become void.
Keywords: الشريعة الإسلامية -- علم الأصول -- الأحكام الفقهية -- مرحلة الطفولة